Pengembangan program layanan bimbingan klasikal untuk meningkatkan daya tarik interpersonal siswa kelas V Sekolah Dasar - Fajar Bilqis (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2019)
Research is motivated by the need for guidance and counseling service programs in increasing interpersonal attractiveness. The limited time of a BK teacher in guiding all students urges the need for the preparation of classical guidance services. The research aims at developing the Classical Guidance Services program in increasing students' interpersonal attractiveness. The research method is development research. After the validation test, this program can be used by the BK teacher or homeroom teacher to increase students' interpersonal attractiveness. The final product of the classical guidance service program consists of the subject and purpose of the intervention, the competency of the counselor or counseling teacher or homeroom teacher, the steps for implementing the classical guidance service, success criteria, tools and media needed, service implementation matrix, and Guidance Service Activity Unit and counseling.